(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The aim of the article. The article highlights the innovative aspect of modern approaches to monitoring the economic security of construction enterprises for the implementation of effective innovation management. The basic principles of the concept of innovative safety as the main component of economic safety of construction enterprises are given. The peculiarities of the influence of innovative factors on the economic safety of the enterprise are analyzed. Proposed, innovative directions of monitoring of economic security at construction enterprises on the basis of evaluation of the current state are offered. The results of the analysis. The monitoring of the economic safety of construction companies is necessary for the full informing of the management about the results of the enterprise’s activity, its effectiveness, on the basis of qualitative quantitative indicators, identification and emergence of possible risks and threats. The monitoring of economic security is interpreted as a system of information base for the adoption of effective management decisions on planning, analysis, control and management. The monitoring of the economic safety of construction enterprises should provide a basic evaluation and analysis system for the timely detection of all threats and risks. The monitoring of the economic safety of the construction company is carried out according to the above mentioned approaches and shows clear results of the activity, but for a more complete picture, the system of economic safety assesses the potential of the enterprise, which determines the main forecasting element and directions of improvement in certain problem areas. The monitoring of the enterprise’s economic security should be investigated in a static and dynamic environment. The state of economic security in the static environment gives a complete assessment of the favorable, prognostic conditions of economic activity, in particular, the dynamic characteristic more accurately considers the policy of changing the safe environment, identifies real threats and gives an opportunity to counteract. Take into account the results of the work performed at the time of evaluation, determine the potential of the facility to protect the company in the future and its uninterrupted functioning. All approaches to monitoring the economic safety of construction companies should be used together, and also involve alternative to the full information characteristics. The monitoring of economic security is carried out on heuristic methods and allocate the functional components of each element to provide the required level of protection. The basic basis for monitoring the economic safety of a construction company stems from its technological features. The innovative component is one of the most essential in the implementation of technologies in the construction industry. Conclusions and directions of further researches. The analysis of the above-mentioned modern approaches to monitoring the economic safety of construction enterprises determines the essence and main tasks of monitoring, diagnostics, analysis, evaluation, based on the calculation of indicators that provide an opportunity to obtain reliable characteristics of the state of economic security at the investigated enterprise. Each approach cannot provide a complete description of economic security, so in practice all approaches are used together. All approaches to monitoring economic security contain significant disadvantages, it is not systematically possible to obtain information, and all methods are general and in one way or another do not take into account the scope of the enterprise, in our case, the construction industry. At domestic enterprises there is no single clear approach and generally accepted rules for monitoring economic security. Our analysis of methodological approaches to monitoring the economic security of construction enterprises requires further development and improvement in the construction industry, and each approach should be clearly elaborated depending on the state of the construction company, which will allow to obtain a full description of economic security, to predict its changes, and to prevent the emergence of crisis phenomena, threats and dangers.